1999
DOI: 10.1021/ma990317n
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Relaxation of Poly(styrene-co-vinylphenol)

Abstract: Dielectric and mechanical measurements of the R-relaxation are reported for polystyrenes of varying vinylphenol content. The presence of the polar moiety substantially increases both the glass transition temperature and the segmental relaxation times of the polymer. However, the shape of the relaxation function, as well as the temperature dependence of the relaxation times, is invariant to copolymer composition. This indicates that the enhanced interactions arising from polar modification of the polystyrene ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 66 publications
(131 reference statements)
2
24
0
Order By: Relevance
“…Such a trend is not unusual, having previously been seen in PVE [58], polyisoprene [59], and PVAc [60]. On the other hand, a b that is nearly independent of temperature is found for many amorphous polymers, including poly(propyleneglycol) [61,62], poly(vinylmethylether) [63,64], and poly(styreneco-vinylphenol) [16].…”
Section: Relaxation Function Breadthmentioning
confidence: 52%
“…Such a trend is not unusual, having previously been seen in PVE [58], polyisoprene [59], and PVAc [60]. On the other hand, a b that is nearly independent of temperature is found for many amorphous polymers, including poly(propyleneglycol) [61,62], poly(vinylmethylether) [63,64], and poly(styreneco-vinylphenol) [16].…”
Section: Relaxation Function Breadthmentioning
confidence: 52%
“…74 Various molecular liquids appear to conform to this idea. 74,75 , although we have shown that the correlation fails for polymers [76][77][78] . In Fig.…”
Section: Resultsmentioning
confidence: 70%
“…͑1͔͒, consistent with the AG model, but without invoking cooperativity. 4 On the other hand, experimental results for polymers [6][7][8][9][10] are at odds with the energy landscape approach per se.…”
Section: Introductionmentioning
confidence: 99%